(untitled) (Education in the 21st Century, 2023)
In this article accreditation of higher education institutions (HEIs) is considered as one of the most significant and applicable mechanisms for ensuring the quality of higher education. The article also analyzes issues related to the enhancement of quality assurance processes, both from theoretical and practical perspectives. Particularly, the problems of the institutional accreditation of HEIs of the RA are discussed in terms of the practical use of the EHEA tools. The problems presented in this article are viewed as obstacles that prevent the continuous improvement, sustainable development of the HEIs and the full integration of the RA into the EHEA.